PENGARUH EMPLOYEE ENGAGEMENT TERHADAP KESIAPAN MENGHADAPI PERUBAHAN ORGANISASI - Hotpascaman Simbolon (Universitas Katolik Soegijapranata, 2017)
The aim of this study was for knowing the impact of employee engagement toward organizational change preparation. The sampling method used in this study was total sampling with 93 people. Hyothesis in this study were confirmedly accepted with statistically regression score 0.877 while the distribution of the data were normal categorization. The result of this study showed that facing the organization change, organization (on this term company) need an engaged employee toward the company.